Back Cover. (8th April 2019) - Gill, Navleen; Leng, Yaozhu; Romero, Roberto; Xu, Yi; Panaitescu, Bogdan; Miller, Derek; Arif, Afrah; Mumuni, Salma; Qureshi, Faisal; Hsu, Chaur‐Dong; Hassan, Sonia S.; Staff, Anne Cathrine; et al.
Abstract : The cover image is based on the Original Article The immunophenotype of decidual macrophages in acute atherosis by Navleen Gill et al., DOI10.1111/aji.13098 .